Ultimate flexural strength of prestressed concrete beams: validation and model error evaluation - MOURA,M. W. (2018)
Abstract In this work a computational model is presented to evaluate the ultimate bending moment capacity of the cross section of reinforced and prestressed concrete beams. The computational routines follow the requirements of NBR 6118: 2014. This model is validated by comparing the results obtained with forty-one experimental tests found in the international bibliography. It is shown that the model is very simple, fast and reaches results very close to the experimental ones, with percentage difference of the order of 5%. This tool proved to be a great ally in the structural analysis of reinforced and prestressed concrete elements, besides it is a simplified alternative to obtain the cross section ultimate bending moment.